Inovasi Pengolahan Sampah Organik Dengan Metode Black Soldier Fly (BSF) Untuk Kemandirian Pangan Lokal - Asri , Fiesca Maini; Wani, Cut Eva (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2024)
Organic waste remains an unresolved environmental issue in many regions. This study aims to examine the effectiveness of organic waste processing innovation using the Black Soldier Fly (BSF) method and its contribution to local food self-sufficiency. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results show that BSF larvae are highly effective in decomposing organic waste, reducing up to 70–80% of waste in a short period. The harvested larvae are used as an alternative animal feed, significantly lowering production costs and improving the productivity of small-scale livestock farming. This innovation also fosters community empowerment and creates new economic opportunities. In conclusion, the BSF method is an environmentally friendly waste management solution that supports sustainable, locally based food resilience.